Speech Audiometry in Galician - Párraga, Alonso; San Román Gómez, Laura (Auditio, 2021)
The phonetic material necessary for determining the threshold of verbal reception and discrimination in adults and children's word lists for discrimination in children are presented, compiled on a digital compact disc for the performance of speech audiometry. Material and method.- We follow the criteria set forth in 1952 by Hirsch, Davis and Silverman (6): equal difficulty between one word and another in the material for verbal reception threshold and for the discrimination material, phonetic composition of each list, curves and preliminary reference parameters, correct recording of selected material, recording calibration method; and the criteria collected by Mª Rosa de Cárdenas and Victoria Marrero (4) to compile and record the lists of words (polysyllables for the threshold and weighted for discrimination) in Spanish and on digital disc. For the Galician language we follow the lists of Dr. Isabel Alvaro (5) in her doctoral thesis, modified and expanded by us. We used a Belton 2000 two-channel audiometer and a compact disc player, applying the standards IEC of 1979 and ISO 8253-3 of 1992. Results.- We present in DC the lists of words in Galician as follows: Track 1 of calibrated, tracks 2 and 3 word lists for determining the speech reception threshold, tracks 4 to 13 word lists for discrimination, tracks 14 to 19 child word lists for discrimination. Conclusions.- We present a phonetic material in Galician that does not exist until now, published on compact disc for the performance of speech audiometry in a stable, reproducible way and with the advantage of being a digital recording.